CONNECTING BRIDGES THROUGH THEATRICAL DESIGN: AN EXAMINATION OF “ASIRI NLA” IN PERFORMANCE - Okeke, Tochukwu J. (UI Scholars Hub, 2019)
The theatre provides an avenue for the expression of very salient and topical issues about a people through the presentation of performances. These performances, which are often in form of plays, are always created by playwrights and that is why playwrights are said to be the watch dogs of the society because their works x-ray past and present situations while proffering solutions for the future. However, the theatre is a composite art which involves the collaboration of many creative artists: Playwright, Director, Stage Manager, Actor(s), Designer(s), amongst others. The designer(s) are the creative artists that interpret the play in visual terms. Their creativity gives a better understanding to the play in performance as the dramatic piece is given further expressions through the actors‟ costumes, properties, lighting and scenery. This essay will interrogated the use of costume and set design in bridging ethnic divides using a Workshop performance of “Asiri Nla” as performed by students of the Department of Theatre and Film Studies, Nnamdi Azikiwe University, Awka at the Arts Theatre. The study found that through an effective set design and appropriate use of costumes that the production was able to unite different peoples under one roof without acrimony thus, it recommended at the effectiveness of design in theatrical productions is a sure way of enhancing national integration.